استخدامات العلاج بالحجامة في الطب الرياضي وتفسيراتها العلمية - خواني, خالد (جامعة الوادي - University of Eloued, 2022)
الحجامة طريقة علاجية قديمة عرفتها مختلف شعوب العالم منذ ألاف السننين، عادت ممارسة الحجامة في مجتمعنا الجزائري بقوة فمارسها الطبيب والمعالج الشعبي وكثر الاقبال عليها، لأن لها خصوصية في المجتمعات العربية والإسلامية كونها تحمل طابعا دينيا، ومن المقبلين على الحجامة نذكر الرياضيين لغرض علاجي أو وقائي لما لمسوه فيها من فوائد وتحسن خاصة في عملية الاسترخاء والراحة النفسية لأنهم يعيشون ضعوطات المنافسات والخوف من الإصابات. تهدف هذه الدراسة إلى التعريف بالحجامة، أنواعها، طرق الاستعمال، والأغراض المستعملة فيها من قبل الرياضيين، كما تناولنا النظريات العلمية الحديثة المفسرة لكيفية تأثير الحجامة على جسم المعالج بها. Hijama is an ancient therapeutic method practiced by different peoples of the world for thousands of years. The practice of the cupping therapy has come back strongly in our Algerian society, it is therefore practiced by doctors and popular medicine, it has a particularity in Arab and Islamic societies because it has a religious character. Several athletes treat with El hijama because they have felt benefits and improvements, especially in the process of relaxation and psychological comfort, as they live under the pressure of competition and fear of injury. This study aims to define the suction cup, its types, methods of use and the purposes used by athletes, and we discussed modern scientific theories explaining the effects of the practice of hijama on human bodies.
The uses of cupping therapy in sports medicine and its scientific explanations
مقال
Keywords: علاج ، حجامة ، طب تكميلي ، طب بديل ، تفسيرات علمية للحجامة; Treatment , cupping, complementary medicine, alternative medicine, scientific explanations for cupping